Teaching Math in the 21st Century, by Barry Garelick [book review] - Richard P. Phelps (Nonpartisan Education Review, 2015)
Barry Garelick recently retired from a long career as an analyst for the Environmental Protection Agency. Probably most individuals toward the end of their careers prepare for a retirement of less work and increased leisure; Garelick attended evening classes to become a public school teacher. (Incidentally, he has written entertainingly about his graduate school experience in earlier publications.) He timed his teacher’s certification to coincide with his retirement from the federal government, moved to the west coast, passed his California licensure examinations in mathematics, and started looking for work.